The function of the endocannabinoid system and glial cells in vivo in patients with first episode psychosis - Laurikainen, Heikki (fi=Turun yliopisto|en=University of Turku|, 2023)
Psychoses are relatively common and often severely debilitating mental disorders with a multifactorial etiological background involving both psychosocial and biological factors. Previously reported associations between the endocannabinoid and immune systems, and psychotic disorders, suggest that they are involved in the etiology of psychosis. Healthy individuals were studied with the selective type 1 endocannabinoid receptor (CB1R) radiotracer [18F]FMPEP-d2, and positron emission tomography (PET), for possible demographic confounders. Radiotracer synthesis and the compound’s behaviour in blood and brain tissues, were in line with reports from previous validation studies. Females had lower availabilities of CB1R than males in 17 discrete brain regions. Separate samples of male patients with first-episode psychosis (FEP) were then studied concurrently in Turku and London, using the CB1R radiotracers [18F]FMPEP-d2 and [11C]MEPPEP respectively. Lower CB1R availability was seen in FEP as compared to healthy controls. The availability of CB1R was also inversely associated with the symptomatology of the psychoses. Translocator protein (TSPO) expression has been postulated to represent glial cell and mitochondrial functions, both of which are influenced by endocannabinoid signalling. Another sample of male and female patients with first episode psychoses was studied using PET with the selective TSPO radiotracer [11C]PBR28. Male and female FEP subjects showed globally lower availability of brain TSPO in comparison to healthy controls. Two concurrent samples of FEP individuals showed persistent elevations of the chemokine CCL22 when compared to population controls. A subgroup of patients with the highest levels of CCL22 also had aberrant levels of other cyto- and chemokines. These results indicate that the immune and brain endocannabinoid systems have become dysregulated in early psychosis. Aberrant glial cell function and/or disturbances in cell metabolism are indicated by the lower availability of TSPO.

Endokannabinoidijärjestelmän ja gliasolujen toiminta ensipsykooseissa Psykoosit ovat verrattain yleisiä, vakavia mielenterveyshäiriöitä, joiden syntyyn vaikuttaa sekä psykososiaaliset että biologiset tekijät. Endokannabinoidi- ja immuunijärjestelmien yhteydet psykooseihin, sekä dopamiinijärjestelmän toimintaan, viittaavat näiden järjestelmien toimivan osana psykoosien etiologiaa. Terveiden koehenkilöiden aivojen endokannabinoidijärjestelmän toimintaa tutkittiin tyypin 1 endokannabinoidireseptorin (CB1R) merkkiaineella [18F]FMPEPd2, ja positroniemissiotomografialla (PET), mahdollisten sekoittavien tekijöiden tunnistamiseksi. Merkkiaineen tuotannon laatua kuvaavat tunnusluvut, sekä merkkiaineen käyttäytyminen veressä ja aivokudoksessa, vastasivat aiempien validointitutkimusten tuloksia. Naiskoehenkilöillä oli alhaisemmat [18F]FMPEP-d2:n jakautumistilavuudet 17 aivoalueella verrattuna miehiin. Miespuolisten ensipsykoosipotilaiden aivojen endokannabinoidijärjestelmän toimintaa tutkittiin erikseen Turussa ja Lontoossa PET:lla vastaavasti CB1R merkkiaineilla [18F]FMPEP-d2 ja [11C]MEPPEP. Molempien otosten ensipsykoosipotilailla oli alhaisemmat merkkiaineiden jakautumistilavuudet verrattuna terveisiin koehenkilöihin. Merkkiaineen sitoutumiselle vapaat CB1R:t olivat lisäksi käänteisesti yhteydessä psykoosioireiden vaikeusasteeseen. Aivojen tukisolujen ja näiden mitokondrioiden toimintaan vaikuttavat sekä endokannabinoidiviestintä, että translokaattoriproteiinin (TSPO) toiminta. Ensipsykoosipotilailla oli kauttaaltaan alhaisemmat TSPO PET merkkiaineen [11C]PBR28 jakautumistilavuudet verrattuna terveisiin verrokkihenkilöihin. Ensipsykoosipotilaiden kemokiini CCL22:n pitoisuudet olivat verrokkien pitoisuuksia korkeammat. Korkeimpia CCL22:n pitoisuuksia omaavien potilaiden immuuniviestintä poikkesi muista verrokki- ja potilastutkittavista laaja-alaisesti. Nämä tulokset osoittavat, että immuuni- ja endokannabinoidijärjestelmät toimivat poikkeavasti ensipsykooseissa. TSPO:n poikkeava toiminta viittaa siihen, että aivojen tukisolut ja/tai solujen aineenvaihdunta häiriintyvät psykooseissa.